Cruising for conspirators : how a New Orleans DA prosecuted the Kennedy assassination as a sex crime - Long, Alecia P., 1966- (Boundless South., 2021)
"New Orleans District Attorney Jim Garrison's decision to arrest Clay Shaw on March 1, 1967 set off a chain of events that culminated in the only prosecution even undertaken in the assassination of John F. Kennedy. Most accounts debate whether a New Orleans-based assassination conspiracy existed. In Cruising for Conspirators, historian Alecia Long shifts to the focus to sexuality, revealing how long-held beliefs about the criminal culpability of homosexuals provided the raw materials for Garrison's investigation and Shaw's selection as a suspect. Her research demonstrates conclusively that the Garrison investigation was birthed in a preoccupation with homosexuality and its relationship to criminality more generally. In turn, the conspiratorial terror the DA cultivated in New Orleans served as a subterranean root system that fed the popular belief in a conspiracy and shaped the works of subsequent authors"--